Latarjet Fixation: A Cadaveric Biomechanical Study Evaluating Cortical and Cannulated Screw Fixation. Issue 4 (19th April 2016) - Alvi, Hasham M.; Monroe, Emily J.; Muriuki, Muturi; Verma, Rajat N.; Marra, Guido; Saltzman, Matthew D.
Background: Attritional bone loss in patients with recurrent anterior instability has successfully been treated with a bone block procedure such as the Latarjet. It has not been previously demonstrated whether cortical or cancellous screws are superior when used for this procedure. Purpose: To assess the strength of stainless steel cortical screws versus stainless steel cannulated cancellous screws in the Latarjet procedure. Study Design: Controlled laboratory study. Methods: Ten fresh-frozen matched-pair shoulder specimens were randomized into 2 separate fixation groups: (1) 3.5-mm stainless steel cortical screws and (2) 4.0-mm stainless steel partially threaded cannulated cancellous screws. Shoulder specimens were dissected free of all soft tissue and a 25% glenoid defect was created. The coracoid process was osteomized, placed at the site of the glenoid defect, and fixed in place with 2 parallel screws. Results: All 10 specimens failed by screw cutout. Nine of 10 specimens failed by progressive displacement with an increased number of cycles. One specimen in the 4.0-mm screw group failed by catastrophic failure on initiation of the testing protocol. The 3.5-mm screws had a mean of 274 cycles (SD, ±171 cycles; range, 10-443 cycles) to failure. The 4.0-mm screws had a mean of 135 cycles (SD, ±141 cycles; range, 0-284 cycles) to failure. There was no statistically significant difference between the 2 types of screws for cycles required to cause failure ( P = .144). Conclusion: There was no statistically significant difference in energy or cycles to failure when comparing the stainless steel cortical screws versus partially threaded cannulated cancellous screws. Clinical Relevance: Latarjet may be performed using cortical or cancellous screws without a clear advantage of either option.